Smartphoneware of the country (New Collegium, 2020)
Now in Ukraine it is necessary to introduce new philosophy of management. It should be administered at most from upstream, and at least from top down activities. It sounds a little absurdly, but that is how the management is organized in wildlife. We believe that with that management philosophy it is possible to reach the situation, when in the first place there will be the requirements of a common man, rather than oligarchs needs. In biological systems the mechanisms of self-regulation, self-management and self-preservation have been generated for millions of years.These mechanisms are based on phenomena of a system of negative and positive feedbacks through upstream signals from cells to the brain. For human society an effective upstream management system can be direct democracy, when the people in the Territories by voting determine how to solve any particular problems of there local life. Referendums and face-to-face interviews with residents are the ways of introducing direct democracy. In the society the formation of new delibarative and executive structures that would be confirmed by law is necessary for implementation of upstream governance mechanisms. The major purpose of new governing bodies should be the fulfillment of objectives for satisfaing the needs of common people. They could be informed above these needs in an electronic format through smartphones. So basically, smartphones can became those nerve fibres that connect an individual with public authorities. The useful function of "smartphoneization" can be associated with the fact that with its help it is possible to bring into force the mechanism of direct democracy in Ukraine, and through it an upstream management system.